2021
DOI: 10.1021/acs.jmedchem.0c01800
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Mimetics Differentially Affect Homologous Chemokines and Attenuate Cancer Development

Abstract: Achieving selective inhibition of chemokine activity by structurally well-defined heparan sulfate (HS) or HS mimetic molecules can provide important insights into their roles in individual physiological and pathological cellular processes. Here, we report a novel tailor-made HS mimetic, which furnishes an exclusive iduronic acid (IdoA) scaffold with different sulfation patterns and oligosaccharide chain lengths as potential ligands to target chemokines. Notably, highly sulfated-IdoA tetrasaccharide (I-45) exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…In a different study, Shanthamurthy C. D. et al synthesized a highly sulfated IdoA-based oligosaccharide as a novel HS mimetic to target chemokines and modulate its activity in cancer progression, and reported its high binding affinity towards several homeostatic and inflammatory chemokines. Additionally, they showed that this HS mimetic, potentially by binding to CCL2, inhibits breast cancer CCL2-mediated cell proliferation and CCR2/CCL2- mediated cell migration, and it reduces cell invasiveness ( 130 ). More recently, Jain P. et al have resorted to a library of HS tetrasaccharide ligands with varying sulfation patterns and high-throughput array binding assays to further address HS binding specificities, and validated two HS analogues, HT-2,6S-NAc and HT-6S-NAc, as potential ligands to target VEGF 165 -mediated cellular events, as these were shown to not only bind with high affinity to the mentioned growth factor but also to inhibit endothelial cells’ VEGF 165 -induced proliferation, migration and tube formation, which are known to be relevant tumour related features ( 131 ).…”
Section: Targeting Of Hs and Hs Biosynthetic Enzymesmentioning
confidence: 99%
“…In a different study, Shanthamurthy C. D. et al synthesized a highly sulfated IdoA-based oligosaccharide as a novel HS mimetic to target chemokines and modulate its activity in cancer progression, and reported its high binding affinity towards several homeostatic and inflammatory chemokines. Additionally, they showed that this HS mimetic, potentially by binding to CCL2, inhibits breast cancer CCL2-mediated cell proliferation and CCR2/CCL2- mediated cell migration, and it reduces cell invasiveness ( 130 ). More recently, Jain P. et al have resorted to a library of HS tetrasaccharide ligands with varying sulfation patterns and high-throughput array binding assays to further address HS binding specificities, and validated two HS analogues, HT-2,6S-NAc and HT-6S-NAc, as potential ligands to target VEGF 165 -mediated cellular events, as these were shown to not only bind with high affinity to the mentioned growth factor but also to inhibit endothelial cells’ VEGF 165 -induced proliferation, migration and tube formation, which are known to be relevant tumour related features ( 131 ).…”
Section: Targeting Of Hs and Hs Biosynthetic Enzymesmentioning
confidence: 99%
“…The following sections are focussed on our efforts over the years to design and synthesize HS mimetics of different structural classes targeted at a variety of diseases. There have been many contributions from various other labs to develop heparin/HS mimetics of various types, including derivatives of native HS sequences, [28] “unnatural” HS sequences, [29] glycopolymers, [30] and non‐carbohydrate small molecules, [10a] to name a few. It is beyond the scope of this account to discuss these in detail.…”
Section: Heparin/heparan Sulfate Mimeticsmentioning
confidence: 99%
“…The antiviral activity against DENV is noteworthy because PG545 inhibits both the Envelope (E) and non‐structural protein 1 (NS1), representing the first identification of a dual targeting drug against DENV infection and NS1 toxicity. The inhibition of cell‐to‐cell spread by PG545 may be linked to its potent inhibition of heparanase, which is known to promote the escape and spread of progeny virions of HS‐binding viruses [29–30] . In addition to blocking virus infectivity, PG545 has also been shown to possess virucidal activity, a unique feature only found in this particular class of amphiphilic HS mimetic.…”
Section: Heparin/heparan Sulfate Mimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] All these events are regulated by specific carbohydrate-protein interactions (CPIs), in which the inherent structural complexity of carbohydrates synergistically modulate the specificity of CPIs; characteristics that affect CPIs are as follows (a) the nature of the glycosidic linkage, (b) the H-bonding network and (c) the conformation plasticity of sugars. [6][7][8][9] However, the carbohydrate-protein binding affinity is weak (in the mili-to micromolar range), resulting in low specificity. [10] To improve the avidity and specificity of this binding event, carbohydrates are decorated on multivalent probes such as nanoparticles (NPs), polymers, dendrimers, bacteriophages and liposomes.…”
Section: Introductionmentioning
confidence: 99%